2011
DOI: 10.1152/ajplung.00187.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary fibroblasts mobilize the membrane-tethered matrix metalloprotease, MT1-MMP, to destructively remodel and invade interstitial type I collagen barriers

Abstract: In acute and chronic lung disease, widespread disruption of tissue architecture underlies compromised pulmonary function. Pulmonary fibroblasts have been implicated as critical effectors of tissue-destructive extracellular matrix (ECM) remodeling by mobilizing a spectrum of proteolytic enzymes. Although efforts to date have focused on the catabolism of type I collagen, the predominant component of the lung interstitial matrix, the key collagenolytic enzymes employed by pulmonary fibroblasts remain unidentified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 64 publications
4
8
0
Order By: Relevance
“…In this study, the ability of NRK cells to invade and migrate into the rat tail Type I collagen matrices was suppressed by BB-94 and GM6001. This is consistent with previous studies using skin or lung fibroblasts (Rowe et al, 2011; Sabeh et al, 2009a) and cancer cells (Zaman et al, 2006), in which BB-94 or similar synthetic MMP inhibitors inhibited most of cell invasion/migration activities in 3D matrices (usually 80~90%). In three-dimensional collagen matrices, proteolytically potent HT-1080 fibrosarcoma and MDA-MB-231 carcinoma cells exhibited a constitutive mesenchymal-type movement including the coclustering of β1 integrins and MT1–MMP at fiber binding sites and the generation of tube-like proteolytic degradation tracks (Wolf et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the ability of NRK cells to invade and migrate into the rat tail Type I collagen matrices was suppressed by BB-94 and GM6001. This is consistent with previous studies using skin or lung fibroblasts (Rowe et al, 2011; Sabeh et al, 2009a) and cancer cells (Zaman et al, 2006), in which BB-94 or similar synthetic MMP inhibitors inhibited most of cell invasion/migration activities in 3D matrices (usually 80~90%). In three-dimensional collagen matrices, proteolytically potent HT-1080 fibrosarcoma and MDA-MB-231 carcinoma cells exhibited a constitutive mesenchymal-type movement including the coclustering of β1 integrins and MT1–MMP at fiber binding sites and the generation of tube-like proteolytic degradation tracks (Wolf et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…MMP14 is a membrane bound enzyme known also known as MT1-MMP that although does not have the classical domain structure of collagenases has been documented as a true collagenase able to degrade collagen fibers [ 61 ]. Moreover, it has been shown that MT1-MMP was the sole proteolytic effector of the invasive activity required by human and mice fibroblasts during trafficking through type-I collagen-riche 3-D barriers [ 62 ]. We have found that in IPF lungs that MMP14 was the most highly expressed of the membrane type MMPs and was expressed by alveolar epithelial cells, however its role in this disease is presently unknown [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…In normal fibroblasts, MT1-MMP is mobilized to the cell surface where it proteolytically remodels pericellular collagen and promotes tissue-invasive activity (35)(36)(37). By contrast, MT1-MMP-null fibroblasts display a complete inability to either degrade or invade type I collagen-rich extracellular matrix barriers (35)(36)(37). As such, primary dermal fibroblasts were isolated from WT, Cartoon, and Mt1-mmp Ϫ/Ϫ mice in order to characterize their respective functional activities.…”
Section: Cartoon Mice Recapitulate An Mt1-mmp ؊/؊ Phenotypementioning
confidence: 99%
“…2, B and C). Likewise, as collagenolytic activity is a prerequisite for supporting invasive activity through native type I collagen hydrogels (35)(36)(37), Cartoon fibroblasts, like MT1-MMP Ϫ/Ϫ fibroblasts, are unable to mount an invasive response (Fig. 2, D and E).…”
Section: Cartoon Mice Recapitulate An Mt1-mmp ؊/؊ Phenotypementioning
confidence: 99%